Terahertz Near‐Field Vortex Beams with Variable Intensity Profiles Based on Geometric Metasurfaces. Issue 12 (18th August 2022) - Zhu, Yang; Zhou, Yiwen; Fan, Zhiyuan; Zang, Xiaofei; Zhu, Yiming; Zhuang, Songlin
Abstract : Electromagnetic waves possessing orbital angular momentum, namely, vortex beams, have attracted considerable attention in the fields ranging from optical communications to quantum science, due to their extraordinary information encoding capabilities. Vortex beams are traditionally exhibited with a doughnut‐shaped intensity distribution, where a null intensity center surrounded by a bright ring, caused by the phase singularity. Herein, geometric metasurface devices that can generate near‐field vortex beams with variable intensity profiles are proposed and experimentally demonstrated. The generation of a vortex beam with tailored intensity profile is realized by integrating the azimuthal nonlinear phase and spiral phase into ring‐shaped anisotropic air‐slit arrays. As proof‐of‐principle examples, multiple geometric metasurfaces that generate vortex beams with C N− fold rotational symmetric or asymmetric intensity profiles in the near‐field are demonstrated in the terahertz domain. This unique capability for terahertz near‐field vortices with variable intensity distributions based on geometric metasurface approach opens an avenue to develop multifunctional integrated systems and system‐on‐chip devices, leading to potential applications in microscopy, integrated photonics, quantum information processing, and optical communication. Abstract : An ultracompact platform is proposed and designed to simultaneously and independently manipulate the helical phase and the corresponding intensity profiles. Unlike the traditional vortex exhibited with a doughnut‐shaped intensity distribution, where a null intensity center surrounded by a bright ring, the proposed metasurfaces can generate near‐field vortex beams with C N− fold rotational symmetric or asymmetric intensity profile in the near‐field region.